The influence of textese on adolescents' perceptions of text message writers. (December 2021) - Kemp, Nenagh; Graham, Jessica; Grieve, Rachel; Beyersmann, Elisabeth
Highlights: Teenagers are often criticised for using 'textese' in digital messages ( c u thurs ). Teens saw messages written by teachers and peers with different levels of textese. They rated others, particularly teachers, more favourably for using less textese. Teenagers have a nuanced understanding of the language of digital communication. Abstract: Text messages are characterised by a casual language style, 'textese' (e.g., c u on thurs ). This study investigated adolescents' perceptions of the use of different levels of textese in digital messages which varied in their intended recipient (friend, teacher). Grade 8 students in Australia ( N  = 90, aged 13–14 years) each read six text messages purportedly written by a fellow student, and rated the extent to which they agreed (on a 7-point Likert scale) that the message writer was intelligent, paid attention to detail, used an appropriate writing style, and was friendly. Overall, participants rated message senders most favourably on all measures when they used no textese, and least favourably when they used high levels of textese. This pattern was even stronger when messages were addressed to teachers rather than same-aged friends. The findings suggest that adolescents are sensitive to both writing style and recipient when considering digital messages.